Assessing the contribution of PIM to strengthening the capacity of developing country representatives to represent their interests in trade negotiations related to agriculture - Bouët, Antoine; Calvo, Facundo; Glauber, Joseph W.; Laborde Debucquet, David; Martin, Will; Parent, Marie; Piñeiro, Valeria; Traoré, Fousseini (International Food Policy Research Institute, 2022)
The purpose of this review is to assess the extent to which the research outputs of Flagship 3, cluster on The Policy Environment for Value Chains (cluster 3.1) of the CGIAR Research Program on Policies, Institutions, and Markets (PIM) have been used to inform decisions and behaviors of representatives of government organizations, development agencies, researchers, donors, private firms, nongovernment organizations, and other users. The assessment both reviews the achievement of past milestones as well as looks forward to how re-searchers should support the trade agenda in developing countries going forward through their research and communication of research and what should be the focus in the research agenda for developing countries. There are already ongoing and forming activities for which strategic guidance, decisions on allocation of resources across activities, or other research decisions could benefit from this assessment. Areas for prioritization include evaluation of policy changes proposed by policymakers or proactively investigated by the PIM trade team (e.g., reduction in domestic support, lowering tariffs), a trade and nutrition database, work on trade and greenhouse gas emissions, future AATM editions, improving data on trade flows, analysis of impactful events such as COVID-19 and large-scale droughts on world markets and value chains, work on the future of trade multilateralism, research on global value chains and non-tariff measures, and research on advancing value chains for competitiveness and economic development.